Left bundle branch pacing preserves ventricular mechanical synchrony better than right ventricular pacing-a two-center study. (19th May 2022) - Mao, YK; Yang, Y; Garweg, C; Sheng, X; Zhang, JF; Yang, Y; Wang, M; Yang, Y; Duchenne, J; Voros, G; Sun, YX; Ma, MM; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Left bundle branch pacing (LBBP) has emerged as a novel pacing method. We sought to evaluate left ventricular (LV) mechanical synchrony under permanent LBBP and compare it with conventional and leadless right ventricular pacing (CRVP, LRVP). Methods: Sixty-four patients with pacing indication for bradycardia were prospectively enrolled. Twenty-two patients received LBBP in the basal ventricular septum. Twenty-three patients received CRVP and 19 LRVP. All patients underwent echocardiography before and after device implantation. Myocardial work was estimated by pressure-strain analysis. Regional work in the septum (SEP) and lateral wall (LW) was calculated as the average from the respective basal and mid-ventricular segments in the apical four-chamber and three-chamber view. The absolute difference between work in LW and SEP (LW-S-work difference) was used as a measure of asymmetry in workload. Results: Baseline characteristics were similar among the three groups. The electrocardiogram during LBBP showed a right bundle branch block pattern; during CRVP and LRVP a left bundle branch block pattern. The paced QRS duration was 114.27±9.9 ms in the LBBP group, significantly shorter than that in the CRVP and LRVP groups (153.9±25.26 ms and 159.1±13.99ms, respectively, both p<0.001). The SEP work decreased in all groups during ventricular pacing (all P<0.05), while the LW work remained similar. The paced LW-S work difference and work difference change between pacing on and off were more significant in the CRVP (1012.9±566.0mmHg*%) and LRVP group (1066.1±472.6mmHg*%) than the LBBP group (260.5±239.8mmHg*%, both P<0.001). In addition, LW-S work difference during ventricular pacing and work difference change between pacing and baseline were comparable in CRVP and LRVP group. Conclusion: LBBP causes less LV dyssynchrony than CRVP and LRVP as it preserves a more physiologic conduction pattern. CRVP and LRVP did not differ in this respect. Further studies need to prove that LBBP has advantages over RVP with regards to preservation of LV synchrony and contractility.